A case study of aerosol impacts on summer convective clouds and precipitation over northern China - Guo, Xueliang; Fu, Danhong; Guo, Xin; Zhang, Chunming (Atmospheric research, 2014)
The emissions such as greenhouse gases, precursor gases and particulate matters may directly alter the Earth radiative budget or indirectly modify cloud and precipitation processes, and possibly induce changes in climate and the hydrological cycle at the regional to global scale. The previous publications reported a few quantitative assessments and inconsistent results on the effects of the emissions on cloud and precipitation. The aerosol properties and possible impacts on a convective precipitation case on 4 July 2008 over the urban region of northern China are investigated based on the Moderate Resolution Imaging Spectroradiometer (MODIS) data and the Weather Research and Forecast (WRF) model coupled with Chemistry (WRF–Chem). Results show that the Aerosol Optical Depth (AOD) is over 0.9 in the study area, indicating a high concentration of aerosol pollution. The value of Angstrom exponent in the study area is larger than 1.0, indicating that the main particles in the area are industrial and biomass burning pollution aerosols with radii less than 0.25–0.5μm. The modeling results show that the domain-averaged precipitation amount under polluted conditions can be increased up to 17% during the whole cloud lifetime. However, the maximum rainfall rate above 30mm/h is enhanced, whereas that below 30mm/h is suppressed in most cloud lifetime. The differences of cloud microphysics and dynamics between polluted and clean conditions indicate that both warm and ice microphysics and updraft are suppressed at the storm's initial and dissipating stages, whereas those at the storm's mature stage are obviously enhanced under polluted conditions. •The aerosol properties and impacts on a convective precipitation clouds are investigated.•The averaged-precipitation under polluted conditions can be increased up to 17%.•The rainfall rate above 30mm/h is enhanced, and that below 30mm/h is suppressed.•Both cloud microphysics and dynamics are influenced under polluted conditions.